Effects of Cooking Method on the Antioxidant Activity and Inhibition of Lipid Peroxidation of the Javanese Salad “Pecel” Vegetables and Its Peanut Sauce Dressing - Gregorius Tsiompah; Retno Murwani; Nani Maharani (International Journal of Food Science)
Vegetables are essential in our diet to maintain health, partly due to their antioxidant properties. A well-known Javanese salad called “Pecel” is prepared by boiling the vegetables and dressed with seasoned peanut sauce. Cooking can reduce or improve the antioxidant properties of foods; therefore, the purpose of this study was to evaluate the effects of brief water boiling (1 min), steaming (1 min), and water blanching (20 s) of the Javanese Pecel vegetables, with or without the peanut sauce. We assessed the in vitro antioxidant capacity and lipid peroxidation inhibition of the salad samples prepared using each cooking method. Six vegetables, i.e., Sesbania grandiflora (turi) flower, Amaranthus hybridus L. (spinach), Carica papaya (papaya) leaves, Cosmos caudatus L. (kenikir) leaves, Vigna unguiculata ssp. Sesquipedalis (yard-long beans), and Vigna radiata (mung-bean) sprouts were cooked by boiling or steaming for 1 min or blanching for 20 s. Peanut (Arachis hypogaea), the raw material for peanut sauce, was fried in either fresh palm oil or repeatedly used palm oil. Our results revealed that the highest antioxidant capacity (percent inhibition of DPPH radicals) was observed following boiling for 1 min in case of spinach (41.94±9.8%), papaya (59.04±5.35%), kenikir (54.93%±6.32%), and yard-long beans (70.21±8.91%); steaming for 1 min in case of turi flower (60.25±3.63%); and blanching for 20 s in case of mung-bean sprouts (49.27±3.69%). Peanut sauce prepared by frying peanuts in fresh or repeatedly used palm oil reduces the natural antioxidant and lipid peroxidation inhibition properties. However, seasoning the peanut sauce with fresh garlic and lime leaves can restore the lost antioxidant properties. Our study provides the first and clear evidence of the optimal cooking method for Pecel vegetables and sheds light on the wisdom behind the existing traditional cooking method.